Intense pulsed white light assisted fabrication of Co-CoOx core-shell nanoflakes on graphite felt for flexible hybrid supercapacitors. (20th August 2017) - Park, Changyong; Hwang, Jeonguk; Hwang, Yeon-Taek; Song, Chiho; Ahn, Suhyun; Kim, Hak-Sung; Ahn, Heejoon
Abstract: In this work, cobalt/cobalt oxide (Co-CoOx) core-shell nanoflakes were directly grown on flexible graphite felt (GF) using a facile one-step intense pulsed white light (IPWL) irradiation method. They were then used as a battery-type positive electrode for a high-performance asymmetric hybrid supercapacitor, which exhibited high rate capability and a long cycle life. The interconnected Co-CoOx thin nanoflakes grown on the GF offer large reaction sites and enough space for easy OH − ion transport due to their 3-dimensionally interconnected network structures. Cobalt metal at the core of the nanoflakes, directly connected to the current collector of the GF, provided pathways for electrons between the cobalt oxide and GF, leading to low internal resistance and high rate capability. The Co-CoOx/GF electrode had a high specific capacity of 108 mAh g −1 at a specific current of 1 A g −1 and maintained a capacity of 71 mAh g −1 at a high specific current of 20 A g −1 . A two-terminal asymmetric hybrid supercapacitor, assembled using Co-CoOx/GF as the positive electrode and activated carbon as the negative electrode with gel-electrolyte (PVA/KOH), exhibited an energy density of 30.1 Wh kg −1 at a power density of 0.86 kW kg −1 and a high retention of 13.0 Wh kg −1 at a power density of 20.4 kW kg −1 . In addition, the asymmetric device showed excellent cycling stability, with 114% capacity retention after 10, 000 cycles.